Characterization of the interaction between the influenza A virus polymerase subunit PB1 and the host nuclear import factor Ran-binding protein 5. - Hutchinson, E; Orr, O; Man Liu, S; Engelhardt, O; Fodor, E (2011)
The influenza A virus RNA polymerase is a heterotrimer that transcribes and replicates the viral genome in the cell nucleus. Newly synthesized RNA polymerase subunits must therefore be imported into the nucleus during an infection. While various models have been proposed for this process, the consensus is that the polymerase basic protein PB1 and polymerase acidic protein PA subunits form a dimer in the cytoplasm and are transported into the nucleus by the beta-importin Ran-binding protein 5 (RanBP5), with the PB2 subunit imported separately to complete the trimeric complex. In this study, we characterized the interaction of PB1 with RanBP5 further and assessed its importance for viral growth. In particular, we found that the N-terminal region of PB1 mediates its binding to RanBP5 and that basic residues in a nuclear localization signal are required for RanBP5 binding. Mutating these basic residues to alanines does not prevent PB1 forming a dimer with PA, but does reduce RanBP5 binding. RanBP5-binding mutations reduce, though do not entirely prevent, the nuclear accumulation of PB1. Furthermore, mutations affecting RanBP5 binding are incompatible with or severely attenuate viral growth, providing further support for a key role for RanBP5 in the influenza A virus life cycle.